2016
DOI: 10.3136/fstr.22.209
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Production of GABA and γ-PGA in a Turmeric and Roasted Soybean Mixture Co-fermented by <i>Bacillus subtilis</i> and <i>Lactobacillus plantarum</i>

Abstract: A turmeric and roasted soybean flour mixture (TRSF) was successfully fermented in solid-state using Bacillus subtilis HA and Lactobacillus plantarum K154. The co-fermentation was optimized using the turmeric mixture Food products made from soybeans, such as tofu, soy sauce, and soybean paste, have been consumed in Asia for a long time. InWestern countries, soy protein is used in processed products such as sausages, hamburgers, breads and pastries (Fukushima, 1981).Soy products are recognized as healthy foods r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
5
1
1
Order By: Relevance
“…Free amino acids in the co-fermented culture broth were determined using HPLC, revealing the complete conversion of glutamic acid to GABA after 5 days of fermentation. The initial glutamic acid content of 20.01 mg/mL in the broth containing 5% skim milk decreased to zero after 5 days, whereas the GABA content increased from none at the beginning to 16.08 mg/mL, which is higher than that reported for a co-fermentation of a soybean/turmeric mixture (Lim et al, 2016).…”
Section: Mucilage and Consistency Of The Hde After The First Fermentationcontrasting
confidence: 56%
See 2 more Smart Citations
“…Free amino acids in the co-fermented culture broth were determined using HPLC, revealing the complete conversion of glutamic acid to GABA after 5 days of fermentation. The initial glutamic acid content of 20.01 mg/mL in the broth containing 5% skim milk decreased to zero after 5 days, whereas the GABA content increased from none at the beginning to 16.08 mg/mL, which is higher than that reported for a co-fermentation of a soybean/turmeric mixture (Lim et al, 2016).…”
Section: Mucilage and Consistency Of The Hde After The First Fermentationcontrasting
confidence: 56%
“…Fermentation of plant products can enrich them with bioactive compounds, enhancing their health benefits (Lim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…plantarum K154. It was found that, in the final stage of fermentation, GABA accumulation from co-fermentation was higher, up to 1.78% more than that of the single-fermented system [112]. B. subtilis HA and Lb.…”
Section: The Co-culture Engineeringmentioning
confidence: 94%
“…천연소재로 GABA는 현미 100 g 당 4-8 mg, 발아현미 10-100 mg으로 자연에서 얻을 수 있는 GABA는 제한적이 며, 젖산균을 이용한 발효물에서 250 mg 이상의 GABA를 함유한다는 연구가 보고되었다 (Hwang, 2011;Mody 등, 1994;Park, 2012). 울금을 이용한 B. subtilis HA와 L. plantarum K154의 혼합발효에서 1.78% GABA 생산이 보고 되었으며 (Lim, 2014), 녹각 추출물을 이용한 L. plantarum EJ2014의 발효에서 1.4%, Leuconostoc mesenteroides SM와 Lactobacillus plantarum K154 균주의 혼합발효에서는 1.23% 의 GABA가 생산되었다고 보고되었다 (Kwon, 2016;Song, Fig. 6.…”
unclassified